Energy Diplomacy in the Eastern Mediterranean: The Cases of EuroAsia and EuroAfrica Interconnector Pipelines of Electricity Interconnection - Tsoukala, Olga (HAPSc Policy Briefs Series, 2022)
The amount of the energy market’s dependence on Russian natural resources, such as natural gas, was discussed during the recent and ongoing Russian invasion of Ukraine. The present study will attempt to document the four-membered energy collaborations in the energy sector between Greece, Israel, Egypt, and Cyprus. This project aims to study the advantages of the interconnection pipelines, “EuroAsia Interconnector” and “EuroAfrica Interconnector” together with the framework of energy diplomacy, which is being built in the Eastern Mediterranean. The present analysis will examine the possible political choices of the already structured relations of the above states, concluding with how they can be the central pillar for the gradual and de facto consolidation of energy autonomy in the Eastern Mediterranean region.